Nutrient Changes and in Vitro Digestibility in Generative Stage of M10-BMR Sorghum Mutant Lines - R. Sriagtula; P.D.M.H. Karti; L. Abdullah; Supriyanto Supriyanto; D. A. Astuti (Faculty of Animal Science, Bogor Agricultural University, 2017)
The objective of this research was to investigate the influences of generative stage on crude protein, crude fiber, ash, and crude fat contents as well as in-vitro dry matter and organic matter digestibilities of M-10 BMR sorghum mutant lines. This research was arranged into a randomized block design with 2 factors. The first factor was M-10 BMR sorghum mutant lines (Patir 3.1, Patir 3.2 and Patir 3.7) and the second factor was generative stages (flowering, soft dough and hard dough phase). The observed variables were proximate contents of stem, leaves and panicle of sorghum plant and in-vitro digestibility of whole plant. The results showed that leaves crude protein (CP) was more influenced by M-10 BMR sorghum mutant lines. Stems and panicles CP were influenced by the interaction between M-10 BMR sorghum mutant lines and generative stages. Further generative stage reduced stems CP but increased panicles CP. Crude fiber (CF), ash, and ether extract (EE) in leaves were not influenced by generative stages. Stems CF was influenced by M-10 BMR sorghum mutant lines and generative stages, while stems EE was more influenced by generative stages. Stems ash content was influenced by the interaction between M-10 BMR sorghum mutant lines and generative stages while panicles ash content was more influenced by generative stages. M-10 BMR sorghum mutant lines and hard dough phase increased in-vitro dry matter and organic matter digestibilities. Based on those findings, it can be concluded that the increased maturity reduces CP and CF contents so it increases in-vitro digestibilities.